Inovação aberta na indústria de semicondutores: uma análise com as design houses brasileiras - Oliveira, Xênia L’amour Campos (2017)
This research aimed to investigate which open innovation practices are adopted by Brazilian design houses in the joint development of integrated circuit designs, based on an adaptation of the model developed by Chesbrough (2012) and Gassmann and Enkel (2004). The methodology adopted was quantitative and qualitative, and the research was divided into two stages. In the first stage, a survey was carried out, with the application of questionnaires with the Brazilian design houses linked to the CI-Brasil program and specialists in microelectronics, as well as documentary analysis, followed by semi structured interviews with some of the participants from the first stage. To analyze the quantitative data descriptive statistics techniques were used, and the chi-square and binomial tests to validate the hypothesis of research, and for the qualitative data, the technique of content analysis was applied. The results showed that the design houses implemented some open innovation practices in the development of integrated circuits projects, with the purpose of assisting in the development of new products, access to new knowledge and competences, besides attracting financial resources, the most frequently adopted techniques were relative to the outside-in process. The results also showed that design houses and specialists in the area seek to control and protect intellectual property through patent registration, however, most respondents affirm that such protection should occur if the innovation developed is economically viable, furthermore, the external partners and their contributions for the companies’ innovation projects were pointed out as important by both the design houses and the specialists in the field. It is also important to highlight the important role played by the government to promote the industry consolidation, through governmental actions and funding agencies to structure public policies.